Performance evaluation of a passive house in sub-arctic climate - Bhattacharjee, Shimantika; Lidelöw, Sofia; Schade, Jutta (Luleå tekniska universitet, Byggkonstruktion och brand, 2018)
As the operational energy use in buildings contributes highly to the total energy used and greenhouse gases emitted in the cold climate regions of Europe, buildings which are more energy-efficient and less carbon-intensive during operation are key to meet sustainability objectives in these regions. Yet, research shows that the practice of passive or low-energy buildings in the sub-arctic climate of northern Sweden is comparatively less than in the southern region. Moreover, previous studies did not explicitly examine the performance of low energy buildings in sub-arctic climate in relation to established building energy efficiency standards. Consequently, knowledge regarding the energy performance of low-energy buildings in such climate is limited. Therefore, the aim is to evaluate the performance, in terms of indoor temperature and energy use for heating, domestic hot water and electricity of a new-built passive house titled “Sjunde Huset” in the sub-arctic town of Kiruna. It is Sweden’s northernmost house designed to fulfil the Swedish passive-house criteria of a maximum heat loss factor of 17 W/m2 and a maximum annual energy use of 63 kWh/m2. The implemented passive design strategies include a highly insulated, compact and airtight building envelope with a vestibule, mechanical ventilation with heat recovery and renewable energy production through photovoltaic solar cells. The house is connected to district heating and is equipped with energy-efficient appliances to allow low occupant energy use. Ongoing performance evaluation is based on building simulation and measurements of energy and temperature in different zones of the building. Energy performance deviations between occupied and non-occupied zones are explored through internal heat gain evaluations. The indoor temperature is also evaluated to assess the temperature variations throughout the year. The ongoing research further evaluate a comparative simulated and measured energy analysis of heating, hot water and electricity based on both the ...